Reliability of a high-pressure die cast Al alloy radiator. (November 2019) - Timelli, Giulio; De Mori, Alessandro; Haghayeghi, Reza
Abstract: The resistance to pressure of a diecast AlSi11Cu2(Fe) alloy radiator has been studied at various holding temperatures. A recently developed method to seal the bottom opening of the radiator element has been presented and its reliability has been even evaluated. Three failure modes are observed during burst testing in the temperature range 40–100 °C, i.e. oil leakage at the interface between the radiator element and the plug, rupture of an element and detachment of the plug from the bottom opening. The main failure mechanism is attributed to the fracture of the radiator element, while the detachment of the plug occurs only at higher temperature; very few leakage failures occur. In the considered experimental range, the temperature exposure affects the burst pressure of the radiator. The failure probability of radiator can be described by three-parameter Weibull distribution, which has evidenced the reliability of the described sealing system.